Social Structure and Local Wisdom of The Bengkalis Coastal Fisheries Community in Mangrove Forest Management - Rawidiah, Cindy; Kartini, Yeni; Yusuf, Yusmar; Rosaliza, Mita (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
The phenomenon of poverty in coastal communities often intersects with the social structure of the community itself. Effective mangrove management requires an interdisciplinary approach that combines social, cultural, economic, and ecological aspects. Social structure aspects, including social hierarchy, access to resources, local wisdom norms, and community networks, have not been widely integrated into mangrove management analysis. Although local wisdom is an important potential, its integration into mangrove management schemes is still weak. This study aims to analyze how the social structure of coastal communities and their local wisdom contribute to or hinder sustainable mangrove forest management. This study uses the Functionalist theory according to Patron-Client and Geertz's local wisdom theory. The research method uses a library research approach with the help of the Publish or Perish 8 application by searching 150 articles related to the research topic. The results of the study explain that social structure and local wisdom play a very important role in supporting the management and conservation of mangroves in coastal areas. The social structure of coastal communities is commonly seen in the majority of jobs as fishermen with a social structure of bosses or toke, skippers or captains, fishermen laborers or members. In preserving local wisdom, the coastal communities of Bengkalis still believe in myths and customs that have developed in the community, such as the semah laut ritual, ikan terubuk, and the prohibition of cutting young mangroves.